MUSTAQIL TA’LIMNI TASHKIL ETISHDA BULUTLI TEXNOLOGIYALARDAN FOYDALANISH - Allambergenova, G. (SCIENCE and SOCIETY, 2025)
This article analyzes the importance of using cloud technologies in the process of self-directed learning, its pedagogical possibilities, and effectiveness. At the same time, information was provided on methods, tools, advantages, and directions for future development of self-directed learning using cloud technologies.
Keywords: cloud technologies; self-education; educational platforms; pedagogical efficiency; distance learning; educational resources; multimedia; computer science; innovation; automatic evaluation